2017
DOI: 10.1007/s11120-016-0332-0
|View full text |Cite
|
Sign up to set email alerts
|

Gallium ferredoxin as a tool to study the effects of ferredoxin binding to photosystem I without ferredoxin reduction

Abstract: Reduction of ferredoxin by photosystem I (PSI) involves the [4Fe-4S] clusters F and F harbored by PsaC, with F being the direct electron transfer partner of ferredoxin (Fd). Binding of the redox-inactive gallium ferredoxin to PSI was investigated by flash-absorption spectroscopy, studying both the P700 decay and the reduction of the native iron Fd in the presence of Fd. Fd binding resulted in a faster recombination between P700 and (F, F), a slower electron escape from (F, F) to exogenous acceptors, and a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…4), which can be almost perfectly fitted (see red curve and residuals) with 2 exponential components. As previously described [25], this behavior is fully consistent with a simple kinetic scheme, where P700 + decays by recombination with (F A , F B ) -(rate k r ) and slow reduction by the exogenous donor DCPIPH 2 (rate k don. ) and where (F A , F B )decays by recombination with P700 + and by electron escape to oxygen (rate k e ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…4), which can be almost perfectly fitted (see red curve and residuals) with 2 exponential components. As previously described [25], this behavior is fully consistent with a simple kinetic scheme, where P700 + decays by recombination with (F A , F B ) -(rate k r ) and slow reduction by the exogenous donor DCPIPH 2 (rate k don. ) and where (F A , F B )decays by recombination with P700 + and by electron escape to oxygen (rate k e ).…”
Section: Resultssupporting
confidence: 86%
“…leaves were dark-adapted for 15 min to allow relaxation of nonphotochemical quenching. In vitro flash absorption spectroscopy P700 + decay kinetics following a single turnover saturating laser flash was measured at 800 nm in PSI preparations as previously described[25].Measurements were made in Tricine 20 mM pH 8, in the presence of 125 mM sucrose, 5 mM MgCl 2 , 30 mM NaCl, 0.5 mM ascorbate and 5 µM DCPIP. The P700 + decay kinetics were nicely fitted with two exponential components, from which the rates k r and k e of recombination and electron escape from the terminal electron acceptor (F A , F B )were determined as explained in Mignée et al (2017).…”
mentioning
confidence: 99%
“…To show the participation of Fd in the chromorespiratory pathway, a redox‐inactive Fd from Thermosynechoccus elongatus in which the FeS cluster iron is replaced by gallium (Fd‐Ga; Mutoh et al ., ) was added to the chromoplasts. Redox‐inactive Fd has recently been used to study Fd binding to photosystem I blocking Fd reduction (Mignée et al ., ). It can be used as a general tool for the study of Fd‐dependent electron transport reactions.…”
Section: Resultsmentioning
confidence: 97%
“…In the cell, the very negative reduction potential of N0 would limit reduction of PS-CI until the Fd pool is in a highly reduced state (at least 100 times more abundant than PS-CI based on copy per cell estimates) 59,60 , with the close proximity of Fd to N0 providing an electron tunnelling pathway from Fd to N1/N2 29,53 . It remains possible that the potential is altered by the binding of subunits as is observed in R-CI 61 , or the substrate itself, as seen in photosystem I 62,63 . It has been suggested that electron transfer may occur in reverse in PS-CI if the proton motive force is high or the PQ pool is predominantly reduced, such as under decreased CO 2 or fluctuating light intensities 2 .…”
Section: Main Textmentioning
confidence: 99%